Dampak Beban Pajak, Exchange Rate dan Kepemilikan Asing Dalam Pengambilan Keputusan Transfer Pricing - Fiqhy Farizh Ferdiansah; Rodhiyah Rodhiyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The impact of globalization has brought significant changes in economic development in the world, rapid progress in several sectors such as transportation, technology, information and communication makes it easy for companies to develop their business by not only becoming local companies, but transforming into multinational companies. This study aims to test and analyze the effect of tax burden, exchange rate, and foreign ownership on transfer pricing in food and beverage sub-sector companies listed on the IDX for the period 2020-2022. This type of research is correlational research with a quantitative approach. The sample in this amounted to 51 financial reports obtained from 17 food and beverage sub-sector companies listed on the IDX during the 3-year period. The analysis method used is statistical method with the help of IBM SPSS 26 application. The results show that the tax burden and exchange rate partially have a negative effect on transfer pricing, while the foreign ownership variable has a positive effect on transfer pricing, and the tax burden, exchange rate, and foreign ownership variables simultaneously have no effect on transfer pricing.